Systematic Review and Meta-analysis of Pirfenidone, Nintedanib, and Pamrevlumab for the Treatment of Idiopathic Pulmonary Fibrosis - Di Martino, Enrica; Provenzani, Alessio; Vitulo, Patrizio; Polidori, Piera (The Annals of pharmacotherapy, 2021)
The comparative efficacy of pirfenidone, nintedanib, and pamrevlumab in slowing the rate of forced vital capacity (FVC) decline and mortality in patients with idiopathic pulmonary fibrosis (IPF) is unknown. To perform a systematic review and meta-analysis (MA) of these drugs for IPF. We searched CENTRAL, PubMed, EMBASE, ClincalTrials.gov, and the World Health Organization's registry databases up to March 2020. Phase II/III randomized controlled trials in adults with IPF were eligible. The random-effect model was implemented calculating the effect size and respective 95% CI as Cohen's for change from baseline FVC (in percentage predicted and liters) and odds ratio (OR) for 10% reduction in FVC and all-cause mortality (ACM). Six studies were included in the MA. For change from baseline in percentage predicted FVC, the MA indicated that the 3 drugs were more effective than placebo (pirfenidone: =3.30%, 95% CI=2.15-4.45; nintedanib: =3.15%, 95% CI=2.35-3.95; pamrevlumab: =4.30%, 95% CI=0.45-8.15). These results are superimposable to those relating to change from baseline FVC in liters (pirfenidone: =0.09L, 95% CI=0.04-0.14; nintedanib: =0.13L, 95% CI=0.10-0.16; pamrevlumab: =0.20L, 95% CI=0.05-0.35). Each drug had a positive effect on 10% reduction in FVC (pirfenidone: OR=0.57, 95% CI=0.45-0.74; nintedanib: OR=0.66, 95% CI=0.51-0.85; pamrevlumab: OR=0.24, 95% CI=0.08-0.73), but only pirfenidone showed an effect on ACM (OR=0.50; 95% CI=0.31-0.83). This MA provided encouraging results on pamrevlumab efficacy in slowing the decline in FVC compared with pirfenidone and nintedanib. Actually, in phase 3, it could become a potential IPF treatment.